In vitro Regeneration of Ginger (Zingiber officinale Roscoe) (Plant Tissue Culture and Biotechnology, 2019)
An efficient and reproducible in vitro regeneration protocol was established for two varieties of ginger (Z. officinale Roscoe) namely, BARI Ada-1 and Chinese ginger accession number SG876). In case of BARI Ada-1 best result was obtained on MS supplemented with 2.0 mg/l BAP, 0.5 mg/l Kn and 0.5 mg/l NAA. In this combination, 95% rhizome bud explants responded within 6 - 8 days and mean number of shoots per explant was 8.79 ± 0.42. On the other hand, Chinese ginger showed best (90%) shoot regeneration response from the same explants on the same medium and hormonal combinations but in exchange of 0.25 mg/l NAA. In this hormonal composition shoot initiation started within 7 - 8 days of culture and mean number of shoots/explant was 6.83 ± 0.71 after 24 - 27 days of culture. Maximum root induction (90 and 80%) was found on MS supplemented with 0.5 mg/l IBA and 0.5 mg/l NAA in case of BARI Ada-1 and Chinese ginger, respectively. The in vitro regenerated plantlets were successfully transplanted into the soil after acclimatization.